Analysis of Language Errors in Student Written Exposition Texts Class VIII of Bontocani 2 Public Middle School, Bone Regency - S, Herawati Arief; Jumriati, Jumriati (Edumaspul: Jurnal Pendidikan, 2023)
This research aims to correct linguistic errors in exposition texts written by class VIII students of SMP Negeri 2 Bontocani, Bone Regency. This research is a qualitative descriptive study. Qualitative research is a research procedure that produces descriptive data, in the form of written or spoken words from people and observable behavior. The data for this research is data from students’ work sheets writing exposition texts. The data source in this research is class VIII students of SMP Negeri 2 Bontocani, Bone Regency. The data collection technique used was reviewing documents in the form of student exposition texts. The results of the research show that the language errors of class VIII students of SMP Negeri 2 Bontocani, Bone Regency include errors in linguistic elements, namely the use of diction or word choice, the use of spelling, the use of conjunctions, the use of verbs, the use of reference words, the use of sentence structure, and the use of words persuasive.